Exploring the role of social media in artrepreneurship: initial empirical insights - George, Ajimon; Mathew, Maria Susan (Frontiers in Communication, 2025)
Artrepreneurship is the process of bringing an artist’s creative capabilities into a physical form so that it can be commercialized widely. Social media can be used as a tool to leverage artrepreneurial ventures. The paper analyses the influence of social media on artrepreneurial practices in a purely inductive approach. The paper is based on the results of a pilot study conducted through semi-structured interviews using a phenomenological qualitative design from 15 respondents, focusing on their views on social media usage and outcomes derived. Data was analysed using NVIVO 14 based on thematic analysis, which generated the following themes: Social media usage, Artistic expression and content strategy, audience engagement and interactions, perceived benefits and challenges and Artrepreneurial outcomes. Findings suggest that social media acts as a catalyst in creative entrepreneurship by acting as a strategic enabler tool. The study contributes to literature on digital entrepreneurship and offers insights for future quantitative research, scale development and practical guidance for artists in the digital.